2021
DOI: 10.1016/j.isci.2021.102647
|View full text |Cite
|
Sign up to set email alerts
|

Artificial humic substances improve microbial activity for binding CO2

Abstract: Highlights Artificial humic acid and fulvic acid were synthesized from agricultural litter With long-term culture, C increment was up to 70 times the chemically added dose High-throughput sequencing shows that Rubrivivax gelatinosus induces C sequestration Application of artificial humic substance induces massive secondary photosynthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…8b, 8c and Please do not adjust margins Please do not adjust margins 8d). This is the typical, well reported texture of humic acid/clay conjugates, 26,27 i.e. we are in the hydrothermal humification range.…”
Section: The Disperse/solid Phasesupporting
confidence: 77%
“…8b, 8c and Please do not adjust margins Please do not adjust margins 8d). This is the typical, well reported texture of humic acid/clay conjugates, 26,27 i.e. we are in the hydrothermal humification range.…”
Section: The Disperse/solid Phasesupporting
confidence: 77%
“…It was further explained that it is possible that in the structure of humic substances there are hormone-like substances, which are directly involved in photosynthesis, respiration, protein synthesis, and other enzymatic reactions [53]. Application of HA into the soil can also increase the population and activity of microorganisms, as well as improve the rhizosphere, which is accelerated by the presence of root exudates [54,55]. This allows plant roots to explore a wider volume of soil, while supporting plant adaptation to suboptimal soil conditions that have low nutrient content and lack of water.…”
Section: Response Of Growth and Nutrient Uptake Of Maize In Greenhousementioning
confidence: 99%
“…The chemical characteristics of artificial H-LPs regulate the metabolism of microbes and plants to affect the soil carbon reservoir (Wei et al, 2021;Yang et al, 2021). A study by Tang et al (2021) revealed that artificial H-LPs promoted carbon sequestration in black soil by stimulating microbial activities for binding CO 2 , thereby increasing nutrient availability for crop growth. In addition, artificial H-LPs can also enhance photosynthesis to transform more CO 2 into organic matter (Tang et al, 2022).…”
Section: Organic Carbon Storagementioning
confidence: 99%